Optimizing green ferrate (VI) modification towards flotation separation of waste polyvinylchloride and acrylonitrile-butadiene-styrene mixtures - Wang, Jianchao (Waste management (New York, N.Y.), 2020)
Copyright © 2019 Elsevier Ltd. All rights reserved.